TANGGUNG JAWAB HUKUM ALGORITMA AI DALAM TRANSAKSI EKONOMI DIGITAL: ANALISIS YURIDIS TERHADAP WANPRESTASI OTOMATIS DAN PERLINDUNGAN KONSUMEN DI PLATFORM E-COMMERCE - Gunawan Widjaja (Jurnal Ekonomi dan Bisnis, 2026)
The development of artificial intelligence (AI) in digital economic transactions has given rise to a new legal phenomenon known as ‘automatic breach of contract’, namely the failure to fulfil contractual obligations resulting from algorithmic decisions without direct human intervention. This study aims to analyse the legal liability of AI algorithms in e-commerce transactions and the effectiveness of consumer protection against risks posed by AI-based automated systems. Employing a normative legal research method with a literature review approach, this study analyses Indonesian legislation, legal doctrine, and relevant literature. The findings indicate that legal liability for automatic breach of contract remains with the e-commerce platform operator as the operator of an electronic system under Law No. 19 of 2016 on Information and Electronic Transactions in conjunction with Government Regulation No. 71 of 2019, with the application of the principle of strict liability (strict liability) analogous to Article 1367 of the Civil Code. However, consumer protection remains hampered by a lack of specific regulations regarding algorithmic transparency, evidentiary mechanisms, and the accountability of automated systems, leaving consumers vulnerable to price discrimination, behavioural manipulation, and data privacy breaches. This study recommends comprehensive regulatory updates through amendments to Law No. 8 of 1999 on Consumer Protection or a dedicated AI regulation establishing obligations regarding transparency, independent algorithmic audits, the reversal of the burden of proof, and the strengthening of consumer protection agencies’ capacity to ensure justice and legal certainty within Indonesia’s digital economy ecosystem.